Perception of nurses’ Empowerment in healthcare organization settings - Neves, Nuno (2016)
Introduction: The concept of Empowerment in nursing has been increasingly used and analyzed in academic literature. It is a concept that nurses, leaders and managers of healthcare institutions should be interested in and should greatly explore. The perception that nurses have of Empowerment plays a decisive role in the organizational results, in the increase in professional autonomy, in collective and individual power increment and in patients’ healthcare providing. Objectives: To evaluate nurses’ perception of Empowerment (Psychological and Structural); to identify the factors that will influence this kind of perception and to reflect on the consequences of that perception. Methods: Quantitative study, based on a sample composed of 269 nurses, mainly female (76,6%), aged between 21 and 59, with a 40,36 years old average age. 68.8% of the participants have a college degree and are working in a hospital in the Beira Alta region, in Portugal. Results: In nurses, the perception of Psychological Empowerment is associated with the perception of Structural Empowerment. Older nurses and nurses who have a longer nursing career show higher competence and lower opportunity. Nurses who have spent a longer period of time in their current services show higher competence but less opportunity, information, support and, globally, a lower Structural Empowerment. In this professional category, specialist nurses’ opinion about information, resources and informal power is quite different from the one felt by the other nurses. Conclusion: Nurses show high levels of Psychological Empowerment and low levels of Structural Empowerment.